Copper and Bronze Working in Early through Middle Bronze Age Cyprus - Balthazar, Judith Weinstein (1986)
Ph.D. Dissertation; Supervisor: James D. Muhly. Order No. DA8703177; DissAbstr 47/10 (April 1987) 3793-A.